COMP: An endogenous thrombin inhibitor - Metharom, P.; Berndt, Michael (American Society of Hematology, 2015)
In this issue of Blood, Liang and colleagues1 demonstrate that cartilage oligomeric matrix protein (COMP) acts as a major endogenous plasma- and platelet-derived inhibitor of thrombin activity in vitro and in vivo.